PKM: Penyuluhan tentang Pelaporan Keuangan pada UMKM Dapur Aura dan UMKM Sayur Kriyur di Kecamatan Selo Kabupaten Boyolali - Putri, Fiani Lindia; Mardiyanto, Doni; Ismawati, Kun; Atas Aji, Ambyah; Giyono, Giyono; Savitri, Savitri; Nugroho, Ignatius Novie Endi; Candrakusuma, Desy Amalia; Widayani, Astrid; Budiwinarto, Kim (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The service was carried out based on findings from the Dapur Aura UMKM and Sayur Kriyur UMKM whose bookkeeping was still in the form of cash flow report only. The aim of this activity is to develop the bookkeeping of the two MSMEs, so that they can start making general journals, compiling ledgers, including balance sheets, income statements and notes to financial reports in accordance with the provisions in SAK EMKM. The service method is carried out through simple counseling to business owners or managers and several financial employees. The result of this activity is an increase in the understanding of MSME managers in running a business, especially regarding financial management, so that they can produce their own simple financial reports, and an article in this journal.